Optimalisasi e-Katalog Laboratorium IPA terhadap Peningkatan Kemampuan Dasar Laboratorium Mahasiswa Pendidikan IPA Universitas Negeri Malang - Anggi Arista, Rini; Nida, Safwatun; Nugraheni, Dian; Nurul Qomaliyah, Eka; Mulyati, Yayuk; Sugiyanto; Nabilah, Wardah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Learning Natural Sciences (IPA) in tertiary institutions has a vital role in forming basic scientific understanding and skills in students. One of the innovations needed to improve students' basic laboratory capabilities is developing learning media in laboratory e-catalogs. E-catalog is an electronic-based information system that provides information regarding tools, materials, and equipment available in the laboratory, including information related to laboratory safety. It allows students to access information in a structured and easy-to-access manner. This research aims to assess the effectiveness of a laboratory e-catalog in improving students' understanding and basic laboratory skills using a questionnaire method for 59 respondents from Science Education students in Biochemistry and Genetics courses. Based on data from evaluation results using the questionnaire method, it shows that the science education department's laboratory e-catalog has proven to be effective in increasing students' knowledge regarding the use and storage techniques of laboratory equipment and materials, which can increase students' knowledge regarding basic laboratory capabilities which influence students' interest in learning and the learning process.